Pengaruh An alisis Jabatan Dan Analisis Kerja Terhadap Rekrutmen Karyawan Pt. Aryateknik Makmursentosa - Cleren Cleren; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (STIE AMKOP, 2022)
The existence of demands in improving human resources requires a company to carry out several activities, the first activity that must be carried out is: recruitment. Position analysis is indeed very important in organizations to place people in a certain position or job. The recruitment system is also preceded by a job analysis to obtain information about job descriptions and position descriptions so that the type and number of human resources needed is in accordance with the needs and qualifications desired by the organization. The purpose of this study was to determine the effect of position analysis and job analysis on employee recruitment at PT. Aryateknik Makmursentosa Medan. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is employees of PT. Aryateknik Makmursentosa Medan. The sample in the study to be tested is 37 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. The results of this study indicate that simultaneously and partially Position Analysis and Job Analysis have an effect on the recruitment of employees of PT. Aryateknik Makmursentosa Medan. Position Analysis and Job Analysis explain their influence on the recruitment of employees of PT. Aryateknik Makmursentosa Medan with a coefficient of determination of 0.521 which means that 52.1% of the recruitment variables can be explained by job analysis and job analysis variables and the remaining 47.9% is varied by other factors not examined such as: work performance, communication and so on. Keywords: Position Analysis, Job Analysis, Recruitment